Step * 1 1 of Lemma bag-summation-single-non-zero


1. Type
2. eq EqDecider(T)
3. Type
4. add R ⟶ R ⟶ R
5. zero R
6. bag(T)
7. ∀[p:T ⟶ 𝔹]. ∀[f:T ⟶ R].
     Σ(x∈b). f[x] (x∈[x∈b|p[x]]). f[x] add Σ(x∈[x∈b|¬bp[x]]). f[x]) ∈ supposing IsMonoid(R;add;zero) ∧ Comm(R;add)
8. T ⟶ R
9. IsMonoid(R;add;zero)
10. Comm(R;add)
11. T
12. ∀x:T. (x ↓∈  ((x z ∈ T) ∨ (f[x] zero ∈ R)))
13. Σ(x∈b). f[x] (x∈[x∈b|eq z]). f[x] add Σ(x∈[x∈b|¬b(eq z)]). f[x]) ∈ R
14. {x:T| ↑¬b(eq z)} 
15. x ↓∈ [x∈b|¬b(eq z)]
⊢ f[x] zero ∈ R
BY
TACTIC:(BagMemberD (-1)
          THEN DVar `x'
          THEN RW assert_pushdownC (-2)
          THEN Auto
          THEN OnMaybeHyp 12 (\h. ((InstHyp [⌜x⌝h⋅ THENM -1) THEN Complete (Auto)))) }


Latex:


Latex:

1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  R  :  Type
4.  add  :  R  {}\mrightarrow{}  R  {}\mrightarrow{}  R
5.  zero  :  R
6.  b  :  bag(T)
7.  \mforall{}[p:T  {}\mrightarrow{}  \mBbbB{}].  \mforall{}[f:T  {}\mrightarrow{}  R].
          \mSigma{}(x\mmember{}b).  f[x]  =  (\mSigma{}(x\mmember{}[x\mmember{}b|p[x]]).  f[x]  add  \mSigma{}(x\mmember{}[x\mmember{}b|\mneg{}\msubb{}p[x]]).  f[x]) 
          supposing  IsMonoid(R;add;zero)  \mwedge{}  Comm(R;add)
8.  f  :  T  {}\mrightarrow{}  R
9.  IsMonoid(R;add;zero)
10.  Comm(R;add)
11.  z  :  T
12.  \mforall{}x:T.  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  ((x  =  z)  \mvee{}  (f[x]  =  zero)))
13.  \mSigma{}(x\mmember{}b).  f[x]  =  (\mSigma{}(x\mmember{}[x\mmember{}b|eq  x  z]).  f[x]  add  \mSigma{}(x\mmember{}[x\mmember{}b|\mneg{}\msubb{}(eq  x  z)]).  f[x])
14.  x  :  \{x:T|  \muparrow{}\mneg{}\msubb{}(eq  x  z)\} 
15.  x  \mdownarrow{}\mmember{}  [x\mmember{}b|\mneg{}\msubb{}(eq  x  z)]
\mvdash{}  f[x]  =  zero


By


Latex:
TACTIC:(BagMemberD  (-1)
                THEN  DVar  `x'
                THEN  RW  assert\_pushdownC  (-2)
                THEN  Auto
                THEN  OnMaybeHyp  12  (\mbackslash{}h.  ((InstHyp  [\mkleeneopen{}x\mkleeneclose{}]  h\mcdot{}  THENM  D  -1)  THEN  Complete  (Auto))))




Home Index